A review of pulmonary toxicity of different types of quantum dots in environmental and biological systems. (1st December 2022) - Wang, Xiaoli; He, Keyu; Hu, Yuanyuan; Tang, Meng
Abstract: Quantum dots (QDs) are nanoparticles with a particle size of 1–10 nm. Typical QDs are made of compounds such as cadmium sulfide, cadmium selenide, silver sulfide, and indium phosphide, among others. QDs exhibit promising potential for a wide range of applications owing to their excellent optical properties. With the rise in the application of and demand for QDs, QDs accumulation in the environment has increased markedly. QDs enter the pulmonary system via inhalation and trigger pulmonary toxicity. This paper first reviews the pulmonary toxicity of different types of QDs in vivo and in vitro. Regarding acute toxicity, QDs cause changes in cell morphology, cell membrane disruption, cell viability, and pulmonary inflammation. Regarding chronic toxicity, cadmium-based QDs cause pulmonary granulomas and have a potential carcinogenic risk. Second, this paper presents an overview of the pulmonary toxicity mechanism of QDs, involving oxidative stress, inflammation, autophagy, apoptosis, and ferroptosis. It summarizes mitogen-activated protein kinases, nuclear factor κB, nuclear factor-erythroid 2-related factor 2, P53, and Phosphoinositide 3-kinase/AKT signaling pathways in apoptosis and autophagy. Third, it enumerates the physicochemical properties of QDs influencing pulmonary toxicity, ranging from components, surface functional groups, size, and surface charge. Lastly, it outlines the shortcomings of current studies on QDs pulmonary toxicity. The paper concludes with a recommendation discussing research-based improvements in the physicochemical properties of QDs to reduce their release in the environment. Highlights: Introduce pulmonary toxicity of different types of QDs in vivo and vitro. Reviews the mechanism of pulmonary toxicity induced by QDs. Summarize four physicochemical properties influencing pulmonary toxicity of QDs. Propose the challenges of pulmonary toxicity assessment of QDs.